The Distribution of Personal Names in the Land of Israel and Transjordan during the Iron II Period. - GOLUB, MITKA (Journal of the American Oriental Society)
This study reports the geographical distribution of personal names in the Land of Israel and Transjordan during the Iron II Period (ca. tenth century B.c.E. to 586 B.C.E., according to the traditional chronology). In contrast with previous onomas-tic studies, the emphasis here is geographic and therefore only names from archaeological excavations are used. 799 names from 66 sites are collected and grouped as theophoric names, hypocoristic (abbreviated) theophoric names, or other. The theophoric names are further sorted into seven subgroups comprising the five theophoric elements yhw, yh, yw, b'l, 'l divine appellatives, and god names other than Yahweh. Finally, the data are presented in a series of maps showing the geographic distribution of name types and its evolution over time. This work shows how names can be used to track historical ethnic trends, yhw and yh are unique Judean elements. Furthermore, names from major Judean sites show a characteristic mixture of theophoric elements that is substantially unchanged across all the Judean sites studied but different from that found in Samaria. Additionally, yw is an element unique to Israel and the b'l element is also found there. 'l is a dominant but not unique Ammonite element. Qws is a unique Edomite element. The use of god names other than Yahweh in ancient Israel was very limited.